PENGEMBANGAN MEDIA BERBASIS GENIALLY DALAM PEMBELAJARAN BERDIFERENSIASI KURIKULUM MERDEKA PADA IPAS KELAS V SD - Dali Mutiara; Atang Sutisna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to develop Genially-based learning media to support differentiated learning in the Independent Curriculum in Natural and Social Sciences (IPAS) subjects for class V students at SDN Gunungkeling. The Merdeka Curriculum emphasizes independent learning and is adapted to student needs, but its implementation has experienced obstacles, including a lack of supportive learning media. This research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Media that develops references in student and teacher books and is designed with an attractive visual appearance, equipped with audio, animated video and game-based evaluation to support interactive learning. The validation results show that this media is very suitable for use, with a score of 90% for media validation and 97% for material validation. The implementation of Genially-based media in the classroom resulted in a significant increase in student understanding, with an average pretest score of 63.00 and posttest 84.60. Statistical tests show that this media is effective in improving student learning outcomes, making it a useful tool to support differentiated learning in accordance with the principles of the Independent Curriculum.